DDRE-02. PATIENTS WITH LEPTOMENINGEAL METASTASES FROM NSCLC BENEFITED FROM INTRATHECAL PEMETREXED AFTER FAILURE TO TYROSINE KINASE INHIBITORS: TWO CASE REPORTS. (12th November 2021) - Ye, Minting; Wen, Lei; Zhou, Jiangfen; Cai, Linbo
Abstract: BACKGROUND: The incidence of leptomeningeal metastasis (LM) is 3%-5% in NSCLC patients; the incidence is even higher in patients with EGFR mutations or ALK gene rearrangement. The prognosis of NSCLC patients with LM is poor with an overall survival (OS) of 3 months with contemporary treatment. METHODS: Here we report two cases of patients with leptomeningeal metastases from NSCLC who benefited from intrathecal pemetrexed after failure to tyrosine kinase inhibitors(TKIs). RESULTS: A 53-year-old woman, diagnosed with adenocarcinoma of the lung with ALK rearrangement, suffered form right limb weakness, dysphagia after multi-line targeted therapy and radiotherapy for brain metastases. Evaluation revealed a rapidly progressing right brainstem mass and diffuse leptomeningeal enhanced. And cytological examination of CSF showed neoplastic cells, which definitely diagnosed as LM. After first intrathecal injection of 30mg pemetrexed every three weeks, the patient's symptoms improved. There were no significant treatment side effects and the quality of life was not affected during the five subsequent treatments. Another patient was a 32-year-old man, diagnosed with adenocarcinoma of the lung with EGFR E24-RAD51E4 fusion mutation with KPS score 30. LM was confirmed after multiline therapy. He suffered form blurred vision and drooping eyelid. Similarly, after first intrathecal injection of 20mg pemetrexed every week, the patient's symptoms improved and KPS score increased gradually. And level II leukopenia was detected during subsequent treatments. Combined with intrathecal pemetrexed progression-free survival (PFS) were 3 months in two NSCLC patients with LM harboring ALK/EGFR mutation . And the quality of life of patients were effectively increased. CONCLUSION: Combination therapy third generation EGFR/ALK agents with intrathecal chemotherapy might be benefited in overall survival.